ESTIMASI PANAS GAMMA PADA PRODUKSI RADIOISOTOP Lu-177, Ir-192, DAN Au-198 DI TERAS MOLIBDENUM RSG-GAS - Riskiana, Dewi Nur; Rohanda, Anis; Abdullatif, R Farzand (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Gamma heating is an important issue related to the irradiation safety of a reactor and its irradiated samples. Gamma heat is generated from the interaction of gamma energy with the target material. The gamma energy produced from the reactor has different gamma energy determined by the fuel type. Uranium molybdenum (UMo) is a future fuel that has several advantages over uranium oxide (UO2) and silicide (USi), one of which to increase the reactor operatingtime. For this reason, a computational study of the RSG-GAS gamma heat with UMo fuel was carried out in several radioisotope productions such as the Lu-177, Ir-192, and Au-198. This study uses the ORIGEN code to calculate the gamma energy produced for UMo fuel types. Gamma heat estimation uses the Gamset program, designed and tested to calculate gamma heat in RSG-GAS. UMo-fueled gamma heat calculation results in RSG-GAS are 4.85 W/g 8.69 W/g. This result is smaller than the gamma heat of uranium silicide (USi), which is around 9.27 W/g 13.3 W/g. The radioisotope Lu-177 has the highest gamma heat of 8.69 W/g, followed by Au-198 and Ir-192, which are 5.89 W/g and 7.12 W/g, respectively. The gamma heat of the three radioisotopes produced by RSG-GAS with UMo fuel does not exceed the maximum gamma heat (20 W/g) that has been determined to ensure that it is safe for the reactor and samples.